Recent Publications (Quarterly Journal of Economics, 1965)
Recent Publications The Quarterly Journal of Economics, Volume 79, Issue 2, May 1965, Pages 328–336, https://doi.org/10.1093/qje/79.2.328 Published: 01 May 1965